A Phase 1/2 Study of a Respiratory Syncytial Virus Prefusion F Vaccine With and Without Adjuvant in Healthy Older Adults. (11th May 2022) - Baber, James; Arya, Mark; Moodley, Yuben; Jaques, Anna; Jiang, Qin; Swanson, Kena A; Cooper, David; Maddur, Mohan S; Loschko, Jakob; Gurtman, Alejandra; Jansen, Kathrin U; Gruber, William C; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is an important cause of disease in older adults. We evaluated the safety and immunogenicity of a stabilized RSV prefusion F subunit (RSVpreF) vaccine candidate with/without adjuvant in adults aged 65–85 years. Methods: Primary cohort participants were equally randomized to 1 of 7 RSVpreF formulations: 60 µg with either Al(OH)3 or CpG/Al(OH)3, 120 µg with either Al(OH)3 or CpG/Al(OH)3, 240 µg with either Al(OH)3 or CpG/Al(OH)3, 240 µg unadjuvanted, or placebo, administered concomitantly with high-dose seasonal inactivated influenza vaccine (SIIV). Participants in the month 0, 2 cohort were randomized to RSVpreF 240 µg with CpG/Al(OH)3 or placebo, administered at months 0 and 2. Results: All RSVpreF vaccine candidates elicited robust and persistent serum neutralizing responses when administered alone or with SIIV. There was no notable difference in neutralizing response between the formulations, including those containing CpG. In the month 0, 2 cohort, there was no booster effect of dose 2. SIIV responses were similar or slightly lower with concomitant administration of RSVpreF. Most systemic and local reactions were mild and more frequent after RSVpreF than placebo. Conclusions: RSVpreF formulations were well tolerated and elicited robust neutralizing responses in older adults; however, CpG/Al(OH)3 did not further enhance responses. Clinical Trials Registration . NCT03572062. Abstract : A stabilized RSV prefusion F subunit (RSVpreF) vaccine candidate with/without adjuvant was evaluated in adults aged 65–85 years. RSVpreF vaccine candidates were well tolerated and elicited robust and persistent serum neutralizing responses; adjuvanted formulations did not further enhance responses.